Does stress transmission in forelands depend on structural style? Distinctive stress magnitudes during Sevier thin-skinned and Laramide thick-skinned layer-parallel shortening in the Bighorn Basin (USA) revealed by stylolite and calcite twinning paleopiezometry - Beaudoin, Nicolas; Lacombe, Olivier; David, Marie-Eleonore; Köhn, Daniel (Terra Nova, 2020)
The Sheep Mountain-Little Sheep Mountain Anticlines, Bighorn Basin (USA) formed as basement-cored Laramide structures in the formerly undeformed foreland of the thin-skinned Sevier orogen. We take advantage of the well-constrained microstructural network there to reconstruct differential stress magnitudes that prevailed during both Sevier and Laramide layer-parallel shortening (LPS), before the onset of large-scale folding. Differential stress magnitudes determined from tectonic stylolites are compared and combined to previous stress estimates from calcite twinning paleopiezometry in the same formations. During stress loading related to LPS, differential stress magnitudes transmitted from the distant Sevier thin-skinned orogen into the sedimentary cover of the Bighorn basin (11-43 MPa) are higher than the differential stress magnitudes accompanying the early stage of LPS related to the thick-skinned Laramide deformation (2-19 MPa). This study illustrates that the tectonic style of an orogen affects the transmission of early orogenic stress into the stable continental interior.
CRIS-Team WoS Importer:2020-02-14